Individual and combined heat and UV-C radiation hurdles against Escherichia coli O157 H7, Salmonella enterica, and listeria monocytogenes in orange juice - Pagal, Gladess A.; Gabriel, Alonzo A.; Rustia, Abigail S.; Villarino, Casiana Blanca J. (Quezon City College of Home Economics, University of the Philippines Diliman, 2019)
Abstract
Thesis (M.S. Food Science)--University of the Philippines Diliman
Keywords: Fruit juices -- Philippines; Orange juice -- Philippines